Performance Analysis of Congestion Control In MANET Using Different Routing Protocols - Ahlawat, Bhawna; Nandal, Vikas (International Journal of Computer Sciences and Engineering, 2019)
Mobile Ad hoc Network (MANET) is an infrastructure free network that is self-configurable and is dynamic in nature. In MANET nodes communicate with each other independently since there is no centralised controller. An extensive variety of routing protocols for MANETs have been suggested by researchers to excel the restrictions of wired routing protocols. Congestion in MANET is a restriction in the implementation of MANET as it can affect the efficiency of the network and may lead to packets loss, increased average delay during transmission or reception of data. This paper discusses various routing protocols to control congestion problem in MANET. Also various performance parameters have been evaluated here like packets transmitted, packets collided, packets that got into error, throughput and average delay by using AODV (Ad- Hoc On Demand Distance Vector), DSR (Dynamic Source Routing) and ZRP (Zone Routing Protocol) protocols by taking 5,10 and 20 nodes using the software NETSIM Simulator.